Faktor – Faktor Yang Mempengaruhi Stres Kerja Karyawan Lembaga Pendidikan Indonesia-Amerika (LPIA) – Cabang Rawasari - Fransiscus Amonio Halawa; Rintis Eko Widodo; M Mushlih Fadhulloh (Journal Management SMC, 2023)
ABSTRACT This research is a quantitative research using ex-post facto method which is a correlational research. Data analysis techniques were carried out using factor analysis including: 1) Correlation of Indicators: Kaiser-Meyer Olkin (KMO), 2) Factor Extraction: Principal Components Analysis, and 3) Factor Rotation: Varimax Method. The population of this study were all employees of the Indonesian – American Educational Institute (LPIA) – Rawasari Branch. The sample for this study was 35 people who were taken using a saturated sample or census technique, in which the entire population was used as a sample. The data collection technique used is a questionnaire (questionnaire). The purpose of this study was to obtain: some of the most dominant factors influencing the work stress of LPIA – Rawasari Branch employees. The results of this study are based on the Factor Analysis of the Principal Component Analysis factor extraction model and the Varimax Method factor rotation, so it can be concluded that some of the most dominant factors influencing work stress of LPIA – Rawasari Branch employees are: (1) Work conflict, (2) Workload, ( 3) working time, (4) task characteristics, (5) group support and (6) leadership influence Keywords: Job Stress, Work conflict, Workload, Working time, Task characteristics, Group support, Leadership influence